2022
DOI: 10.3390/healthcare10020390
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Italian Cross-Sectional Study on the Level of Digital Psychiatry Training, Knowledge, Beliefs and Experiences among Medical Students, Psychiatry Trainees and Professionals

Abstract: The COVID-19 pandemic led to the implementation of digital psychiatry (DP), resulting in the need for a new skilled healthcare workforce. The purpose of this study was to investigate the level of training, knowledge, beliefs, and experiences of young mental health professionals and medical students in DP. An ad hoc cross-sectional survey was administered and descriptive analyses, Student’s t and ANOVA tests were conducted, together with an exploratory factor analysis, bivariate correlations and linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Such training will likely be important to increase acceptance and satisfaction with telepsychiatry going forward. Previous studies have shown that appropriate training in different areas of telemedicine (such as "digital psychiatry") strongly influence providers' perceptions and attitudes regarding the usefulness and effectiveness of remote care (34)(35)(36). Indeed, we observed that all providers who felt they received sufficient initial training and on-going support were more than two times as likely to be satisfied with telepsychiatry.…”
Section: Discussionmentioning
confidence: 59%
“…Such training will likely be important to increase acceptance and satisfaction with telepsychiatry going forward. Previous studies have shown that appropriate training in different areas of telemedicine (such as "digital psychiatry") strongly influence providers' perceptions and attitudes regarding the usefulness and effectiveness of remote care (34)(35)(36). Indeed, we observed that all providers who felt they received sufficient initial training and on-going support were more than two times as likely to be satisfied with telepsychiatry.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, residents can attend several national and international meetings and are involved in variety research projects. In addition, inside the school network, there are also two high-fidelity simulation labs where is possible to implement technical and non-technical skills, has it happened for other disciplines [3,[18][19][20][21][22]. Thanks to all these resources, the school of Modena is accredited by MIUR and currently trains 147 residents, and it has played a strategic role, as reservoir of physicians with a degree of training in A-IC of UNIMORE during many stressful system events such as Emilia-Romagna region (Italy) earthquake in 2012, and during the Vasco Rossi Modena Park ® concert with about 220.000 participants and about 5000 staff members [7].…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, an integrated training track in clinical informatics has been developed at a US psychiatry residency program, though it still does not address digital psychiatry or offer training across the residency program [ 19 ]. A recent survey among Italian learners including psychiatry trainees revealed that nearly 90% of respondents indicated a lack of discussion of digital psychiatry in their academic training, with the majority (54.4%) desiring training on the topic [ 20 ].…”
Section: Introductionmentioning
confidence: 99%